Efecto comparativo de dos tipos de congelación (rápida y lenta) en la cinetica de rehidratación de cubos de tumbo (passiflora mollisima, l) liofilizado. - Silva Balarezo, Cinthya Del Carmen (2015)
A kinetic study of rehydrating tumble drying the freeze-drying method, for two types of freezing liquid and in conventional equipment is presented; refrigerator. The dumps were washed, peeled and cut into submission to freeze and then be dehydrated by lyophilization. The dried cubes were packed in vacuum immediately after removal from the lyophilizer, and then be refrigerated at 4 ° C for 24 hr in order to stabilize the moisture still present in these, after which time he continued to rehydrate, a treatment with distilled water. Rehydration kinetics was carried out over a period of 120 min. The semi-empirical model PELEG where and constant was determined initial rate of hydration and maximum water absorption, respectively to be adjusted to a statistical model, where it was observed that there is no significant difference between the type of applied freeze; however visually remarkable difference was observed in the physical characteristics of the lyophilized lie, and disintegration of particles rehydrated samples from slow freezing.